The Genesis of The Language of Arab Youth in the Modern Era/ نشأة لغة الشباب العربي في العصر الحديث - Hamilah Hasan; Febrian Nafisah Nurul Afida (Universitas Negeri Malang, 2022)
The purpose of writing this journal is to find out the language of young people in modern times, which is influenced by the Arabic language Fusha and Amiyah which are used as the language of the native Arabic. The language user is also influenced by Fusha and Amiyah language differences. In this journal the author also describes the language of Egyptian youth in the early twenty-first century, then the language of women in the 11th century which is also considered to affect the language of young people in modern times. The method used by the authors in this journal is to use a library analysis approach that is describing using theories supported by valid and up-to-date literature. The results of this journal writing are that the components contained in the contents of this journal are all continuous in influencing the language of young people in modern times. كما عرفنا من أهداف كتابة هذا البحث يعني لحث المفارقة في اللغة المتقدمين و اللغة الشباب اليوم نشأتها وتنميتها في العالم مع مرور الحضارة. كما رأينا لاحقا أنّ نشأة الفصحى في قريش واعتمادها على الكثير من خصائص شيئ مختلفة فيه. والفصحى أيضا، هي ظرف لم يتوفر لآية لغة من اللغات العالم أنها ارتبطت القرآن الكريم منذ أربعة عشر قرنا. فنشأة حضارة الشباب تأثرت إلى نشأن لغتهم عمية كانت أو فصحة في المستقبل مع أنهما العربية فشتان بينهما. في هذا الحين بين الباحث أيضا لغة شباب المصريين في بدء أول القرن الحادي والعشرين ثم لغة المرأة التي تأثرت تأثيرا عظيما أيضا نحو شباب اليوم في القرن الحادي عشر. وأما مدخل البحث الذي استخدمه الباحث يعني بحث مكتبي لتحليل مشكلات البحث بنظرية الموافقة مؤلفة كانت وصالحة. وأما الحاصلة من كتابة هذا البحث اجماليا هي مكونات التي اشتملت في هذا البحث كلها اتصاليا بمؤثرة لغة شباب اليوم في عصرنا هذا.